O outono do poder americano - Freitas, Alexandre Jeronimo de (2008)
The main aim of this dissertation is to identify the foundations of the American hegemony, in the economic and political-military fields, highlighting its financial aspects. In order to fulfill this task the Systemic Cycles of Giovanni Arrighi were used. Throughout this analysis, the influence of the economic and financial aspects on the American power are pointed out. First of all, there is a study of the how the finance was conditioned to certain rules established by the Bretton Woods Agreement at the height of the American hegemony. With the end of this agreement and with the American hegemony crisis in the 1970s, the finance started to have more freedom of action. The monetarist counter revolution transformed this freedom into an American government project, with the objective of overcoming its hegemony crisis. The revival of power and wealth in the United States in the 1980s and 1990s transformed this period into an American belle époque . However, that revival might have cost more than the US could afford.